The role of long non-coding RNA LINC00839 in oral squamous cell carcinoma based on bioinformatics and experimental research - Ashkan Kalantary-Charvadeh; Saman Morovat; Somayeh Aslani; Nasrin Ziamajidi; Amirnader Emami Razavi; Roghayeh Abbasalipourkabir (Scientific Reports)
Abstract This study explores the role of LINC00839 and its potential interaction with the miR-195-5p/cyclin E1 (CCNE1) axis in oral squamous cell carcinoma (OSCC). Using The Cancer Genome Atlas, we analyzed lncRNA, miRNA, and mRNA sequencing data for OSCC. Different online tools were applied to detect lncRNA-related miRNAs and their target mRNAs, forming a lncRNA/miRNA/mRNA axis. Co-expression analysis determined the correlation between lncRNA and mRNA expression. Afterward, protein-protein interaction network and functional enrichment analyses disclosed the biological activity of target genes. The expression and correlations of LINC00839, miR-195-5p, and CCNE1 were examined in 30 pairs of OSCC and noncancerous tissues. A Chi-square test was used to determine clinicopathological associations, and ROC analysis estimated diagnostic value. A total of 66 differentially expressed lncRNAs, 80 miRNAs, and 1149 mRNAs were identified in OSCC versus non-tumor samples. After filtering lncRNAs based on novelty, and predicting lncRNA-miRNA, and miRNA-mRNA interactions, the LINC00839/miR-195-5p/CCNE1 axis was discovered. RT-qPCR showed upregulation of LINC00839 and CCNE1 was accompanied by the downregulation of miR-195-5p. A significant positive correlation was observed between LINC00839 and CCNE1 mRNA expression, along with a significant negative correlation between LINC00839 and miR-195-5p expression. Moreover, increased LINC00839 was associated with tumor grade and lymph node status, while decreased miR-195-5p was correlated with lymph, depth, and vascular invasion (p < 0.05). The combined ROC curve demonstrated a significant area under the curve of 0.93. This discovery reveals a novel regulatory mechanism underlying OSCC tumorigenesis and may provide effective diagnosis and potential therapeutic targets to cure this devastating cancer.